(untitled) (Zaporizhzhia Historical Review, 2021)
An accordance of contemporary political and power relations to fundamental principles of the democracy is analyzed. Mutual conditionality of personification and democratic character of political power are disclosed. Using this basis the main principles of the optimization of political and power activity are defined.